Santri’s Perceptions of Discomfort in the Learning Environment and Its Impact on Cognitive Barriers in Arabic Language Learning - ansori, ahmad; Umar Najih Zein; Lukman Habibul Umam (Prodi Pendidikan Bahasa Arab Sekolah Tinggi Agama Islam As-Sunnah, 2025)
This research investigates santri’s lived experiences concerning the comfort of the boarding school environment and its role in shaping their comprehension in Arabic language learning. The study took place at a salafiyah type Islamic boarding school in Central Lampung, characterized by limited study facilities. Employing a qualitative methodology with a hermeneutic phenomenological framework, data were obtained through semi-structured interviews involving seven purposively selected students, two pesantren administrators, and one homeroom teacher. Thematic analysis followed the framework of Miles and Huberman. The study reveals that discomfort arising from physical factors (such as overcrowded spaces and insufficient ventilation) and social factors (such as unsupportive peer interactions) significantly impedes santri’s focus and understanding. However, environmental adjustments such as structured schedules and collective sanitation efforts can foster better cognitive engagement. These findings emphasize the need for a well designed, supportive learning environment in pesantren, especially for effective Arabic language instruction.